Promoting Nrf2/Sirt3-Dependent Mitophagy Suppresses Apoptosis in Nucleus Pulposus Cells and Protects against Intervertebral Disc Degeneration. (10th June 2021) - Hu, Sunli; Zhang, Chenxi; Qian, Tianchen; Bai, Yue; Chen, Liang; Chen, Jiaoxiang; Huang, Chongan; Xie, Chenglong; Wang, Xiangyang; Jin, Haiming
Abstract : One of the causes of intervertebral disc degeneration (IVDD) is nucleus pulposus cell (NPC) death, possibly apoptosis. In this study, we explored the role of the Nrf2/Sirt3 pathway and tert-butylhydroquinone (t-BHQ) in IVDD and elucidated the potential working mechanism. Reactive oxygen species (ROS) assay kits and malondialdehyde (MDA) assay kits were used to assess oxidative stress. Western blot and TUNEL staining were used to examine apoptosis. After siRNA against Nrf2 or lentivirus against Sirt3 was transfected into NPCs, the mechanism of the effect of the Nrf2/Sirt3 pathway on NPCs was assessed. The interaction between t-BHQ and its potential interacting protein NRF2 was further investigated through protein docking analysis. ChIP examined the binding affinity between Nrf2 and Sirt3 promoter. In vivo experiments, X-ray, hematoxylin-eosin (HE) staining, Safranin O staining, and immunohistochemistry were used to evaluate IVDD grades. The results demonstrated that activation of the Nrf2/Sirt3 pathway inhibited tert-butyl hydroperoxide- (TBHP-) induced apoptosis and mitochondrial dysfunction in vitro. In addition to apoptosis, upregulation of the Nrf2/Sirt3 pathway induced by t-BHQ restored TBHP-induced autophagic flux disturbances. However, its protective effect was reversed by chloroquine and Si-ATG5. Furthermore, t-BHQ ameliorated IVDD development in a rat model. In conclusion, our findings indicate that the Nrf2/Sirt3 pathway and its agonist represent a potential candidate for treating IVDD.